Prężność rodzinna – rola zasobów religijnych i duchowych - Moskal, Dominik; Pyrz, Bartosz; Leszczyńska, Weronika (Family resilience – the role of religious and spiritual resources, 2024)
Family resilience is an issue that grew out of research on individual resilience. Family resources have a significant role in its understanding. They enable its members to cope effectively with stressors and to adapt to a reality burdened by the effects of adverse circumstances. Among these are spiritual and religious resources. They enable the family to make meaning of the events associated with the stressor and to see it in terms of a manageable problem. Such resources put the crisis experienced by the family and its coping within a framework of values. This paper aims to analyse the phenomenon of family resilience in the context of the family’s spiritual and religious resources. The most relevant models of family resilience and the characteristics of resilient families are cited. Research findings on the role of spirituality and religiosity in family functioning are referred to. Mechanisms through which religiosity and spirituality can support the family were pointed out. A synthesis of the results of the cited research with the concept of family resilience was made. Possible further research directions are indicated.